2020
DOI: 10.1111/1753-6405.12935
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of sepsis in cancer patients in Victoria, Australia: a population‐based study using linked data

Abstract: Objective:To determine the clinical characteristics, outcomes and longitudinal trends of sepsis occurring in cancer patients. Method:Retrospective study using statewide Victorian Cancer Registry data linked to various administrative datasets.Results: Among 215,763 incident cancer patients, incidence of sepsis within one year of cancer diagnosis was estimated at 6.4%. The incidence of sepsis was higher in men, younger patients, patients diagnosed with haematological malignancies and those with de novo metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 20 publications
(32 reference statements)
4
34
1
Order By: Relevance
“…We commend te Marvelde et al for evaluating sepsis in Victorian cancer patients through linkage of population‐based datasets and state registry data 1 . Using administrative coding data (ICD‐10‐AM) to define sepsis, sepsis incidence for the period 2008‐2015 was estimated to be 6,200 sepsis events per 100,000 cancer patients in Victoria.…”
Section: Published Performance Metrics Of Different Coding Abstractiomentioning
confidence: 99%
See 1 more Smart Citation
“…We commend te Marvelde et al for evaluating sepsis in Victorian cancer patients through linkage of population‐based datasets and state registry data 1 . Using administrative coding data (ICD‐10‐AM) to define sepsis, sepsis incidence for the period 2008‐2015 was estimated to be 6,200 sepsis events per 100,000 cancer patients in Victoria.…”
Section: Published Performance Metrics Of Different Coding Abstractiomentioning
confidence: 99%
“…To date, however, considerable discordance has been identified in sepsis rates calculated using both implicit and explicit coding methods compared to rates defined using clinical criteria (Table 1). 7 In particular, the explicit coding strategy used in te Marvelde et al 1 . has been demonstrated to have lower sensitivity for severe sepsis detection when compared to implicit coding 6 (Table 1).…”
Section: Published Performance Metrics Of Different Coding Abstractiomentioning
confidence: 99%
“…More recent epidemiological data are necessary for two reasons: first, recent studies suggest that the mortality of critically ill cancer patients with sepsis has decreased over time [8]. Second, the incidence of sepsis has been steadily increasing in the general population [9] and also probably in cancer patients: a recent study reported that the incidence of sepsis in cancer patients reached 6.4% within a year [10]. The net result in cancer patients of the increased incidence and decreased mortality of sepsis observed over the past 2 decades is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The net result in cancer patients of the increased incidence and decreased mortality of sepsis observed over the past 2 decades is unknown. The incidence of sepsis seems to peak during the first year after cancer diagnosis [10] probably due to the higher treatment intensity (surgery, chemotherapy); standardized mortality ratios [11] also peak within 1 year, but how much sepsis contributes to this mortality is unclear, as no study has investigated sepsis as a time dependent variable with non-sepsis related death as a competing event. The objective of this study was to update the data on sepsis incidence, to investigate its risk factors (demographics, comorbidities, baseline cancer characteristics) and its contribution to overall mortality within the first year of cancer diagnosis in middle age adults, using competing risk and multistate models.…”
Section: Introductionmentioning
confidence: 99%
“…We would like to thank Valentine et al 1 for taking the time to comment on our article ‘Epidemiology of sepsis in cancer patients in Victoria, Australia: a population‐based study using linked data’, 2 recently published in the Australian and New Zealand Journal of Public Health . We agree that the ability to systematically monitor the incidence of sepsis and its outcomes is important.…”
mentioning
confidence: 99%